Cuprizone-induced oligodendrocyte loss and demyelination impairs recording performance of chronically implanted neural interfaces. (May 2020) - Wellman, Steven M.; Guzman, Kelly; Stieger, Kevin C.; Brink, Lauren E.; Sridhar, Sadhana; Dubaniewicz, Mitchell T.; Li, Lehong; Cambi, Franca; Kozai, Takashi D.Y.
Abstract: Biological inflammation induced during penetrating cortical injury can disrupt functional neuronal and glial activity within the cortex, resulting in potential recording failure of chronically implanted neural interfaces. Oligodendrocytes provide critical support for neuronal health and function through direct contact with neuronal soma and axons within the cortex. Given their fundamental role to regulate neuronal activity via myelin, coupled with their heightened vulnerability to metabolic brain injury due to high energetic demands, oligodendrocytes are hypothesized as a possible source of biological failure in declining recording performances of intracortical microelectrode devices. To determine the extent of their contribution to neuronal activity and function, a cuprizone-inducible model of oligodendrocyte depletion and demyelination in mice was performed prior to microelectrode implantation. At 5 weeks of cuprizone exposure, mice demonstrated significantly reduced cortical oligodendrocyte density and myelin expression. Mice were then implanted with functional recording microelectrodes in the visual cortex and neuronal activity was evaluated up to 7 weeks alongside continued cuprizone administration. Cuprizone-induced oligodendrocyte loss and demyelination was associated with significantly reduced recording performances at the onset of implantation, which remained relatively stable over time. In contast, recording performances for mice on a normal diet were intially elevated before decreasing over time to the recording level of tcuprizone-treated mice. Further electrophysiological analysis revealed deficits in multi-unit firing rates, frequency-dependent disruptions in neuronal oscillations, and altered laminar communication within the cortex of cuprizone-treated mice. Post-mortem immunohistochemistry revealed robust depletion of oligodendrocytes around implanted microelectrode arrays alongside comparable neuronal densities to control mice, suggesting that oligodendrocyte loss was a possible contributor to chronically impaired device performances. This study highlights potentially significant contributions from the oligodendrocyte lineage population concerning the biological integration and long-term functional performance of neural interfacing technology.